Renegotiating family practices post separation an Irish case study - Moore, Elena (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2011)
This study explores changing personal relationships in the aftermath of separation and divorce. Post separation family lives in an Irish context can enlighten us about family life and parenting generally in the 21st century. The research set out to examine the role that gender plays in the renegotiation of family practices post separation, to examine the factors that impact on separating parents' ability to renegotiate family practices and to locate these changes within the wider social and theoretical context of changing personal relationships.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin.